Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2174/157340481101150914202014
|View full text |Cite
|
Sign up to set email alerts
|

Can Group Exercise Programs Improve Health Outcomes in Pregnant Women? A Systematic Review

Abstract: Current scientific evidence supports the recommendation to initiate or continue the practice of physical exercise in healthy pregnant women. Group exercise programs have positive effects in improving health and well-being, as well as social support. In order to understand the scientific evidence in this field, and the outcomes in maternal health, it has generated wide interest in exploring the studies carried out with more relevant group exercise programs. The aim of this systematic review was to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In addition to the previous systematic review [15], this article evaluated intervention design and reported its limitations. The CERT model evaluated the physical exercise program design through key items considered essential to report the replicable capacity of intervention.…”
Section: The Consensus Of Exercise Reporting Template (Cert)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the previous systematic review [15], this article evaluated intervention design and reported its limitations. The CERT model evaluated the physical exercise program design through key items considered essential to report the replicable capacity of intervention.…”
Section: The Consensus Of Exercise Reporting Template (Cert)mentioning
confidence: 99%
“…In 2015, a systematic review was provided to evaluate the available evidence on the effectiveness of group exercise programs in improving women's health outcomes during pregnancy, as well as newborn's health outcomes, and to assess the content of the programs [15]. The present systematic review aims to update the knowledge about the effectiveness of exercise in a group context during pregnancy, between 2015 and 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Main references for this content: systematic review studies. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]…”
Section: Dovepressmentioning
confidence: 99%
“…• Systematic reviews studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] • Official recommendations on physical activity during pregnancy and postpartum 1,[21][22][23][24][25][26][27][28][29][32][33][34][35] • Other studies referenced in the presentation, upon request • Chapters developed in the textbook "Exercise and Physical Activity during Pregnancy and Postpartum", published by Springer in 2019, 51 and the second edition in 2022. 52 To be noted that this is the unique international book addressing this topic, so far.…”
Section: • Active Pregnancy Workhop (Powerpoint Presentation) [Unpubl...mentioning
confidence: 99%
See 1 more Smart Citation